A predictive micromechanically-based model for damage and permanent deformations in copolymer sutures. (March 2021) - Trentadue, F.; De Tommasi, D.; Puglisi, G.
Abstract: An effective description of the mechanical behavior of biodegradable copolymers suture threads requires the analysis of their response under cyclic loading and the prediction of the fundamental damage and residual stretches effects. In this paper we propose a micromechanically-based model adopting a new form of Worm Like Chain free energy for the copolymer chains, which takes care of the insurgence of residual stretches on the basis of a rigorous statistical mechanics result. Under the affinity hypothesis we subsequently derive the macroscopic response of the material. The obtained model has a clear physical interpretation and depends on a small number of parameters, which can be fitted by a simple uniaxial test. The effectiveness of the theoretical results has then been verified by performing cyclic tests on Monocryl® monofilament sutures and showing the ability of the model in predicting with high accuracy the history dependence, the damage and permanent deformations in the obtained response.